Arabic Language Acquisition through Podcast Integration: A Blended Media Approach / اكتساب اللغة العربية من خلال دمج البودكاست: نهج وسائط متعددة مدمجة - Shofi Shadady; Kharima Zahratun Nisa (IJAS: International Journal of Arabic Studies, 2025)
This study explores the integration of podcasts as a digital medium in enhancing Arabic language acquisition among non-native speakers through a blended learning model. By employing a qualitative case study design, the research investigates the experiences of students and teachers in three educational institutions that implemented podcast-based instruction. Findings reveal that podcasts significantly improve students' listening comprehension, vocabulary retention, and oral fluency by providing authentic language exposure and interactive listening experiences. Teachers utilized podcasts flexibly to introduce new topics, reinforce lessons, and promote learner autonomy. Furthermore, the integration of local content into podcast materials contributed to cultural relevance and increased student engagement. Despite challenges such as technological access and the need for teacher training, the overall implementation demonstrated positive pedagogical impacts. The study concludes that podcast integration is a viable and effective tool for Arabic language education in digital learning environments.